The Shards - Ellis, Bret Easton (New York : Alfred A. Knopf, 2023)
"A story about the end of innocence, and the perilous passage from adolescence into adulthood, set in a vibrantly fictionalized Los Angeles in 1981 as a serial killer begins targeting teenagers throughout the city"--.
"This is a Borzoi book"--Title page verso.
New Book 2023 Winter.
Keywords: Murder; Investigations; Serial murders; Los Angeles (Calif.); Novels; Thriller fiction